Synthesis and electro-optic properties of nanosized-boron doped cadmium oxide thin films for solar cell applications - Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2011)
Boron doped CdO thin films were prepared by sol-gel dip coating technique. Atomic force microscopy results indicate that the boron doped CdO films have the nanostructure. The influence of the boron doping on the film growth is resulted in a change of grain size. The optical band gap of the CdO films was significantly changed by boron dopant. The refractive index dispersion of the films obeys the single oscillator model. The dispersion parameters, oscillator and dispersion energy were changed by boron dopant. The optical absorption results show that the optical band gap of the CdO film can be engineered over a wide range of 2.27-2.45 eV by introducing B dopant. For solar cell applications of the CdO film, a p-Si/1% B doped n-CdO heterojunction solar cell was fabricated and the solar cell shows the best values of open circuit voltage, V-oc = 0.37 and short circuit current density, J(sc) = 0.81 mA/cm(2) under AM 1.5 illumination, despite the fact that V-oc and J(sc) are lower than those reported in the literature without using frontal grid contacts and or post-deposition annealing. It is evaluated that this work is useful as a basis search for synthesis of the nanosized-boron doped cadmium oxide thin films for solar cell applications and more competitive p-Si/n-CdO based solar cells. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Nanostructure; CdO film; Sol-gel; Optical constants